1999
DOI: 10.1136/bjo.83.8.929
|View full text |Cite
|
Sign up to set email alerts
|

Causes of childhood blindness in the People's Republic of China: results from 1131 blind school students in 18 provinces

Abstract: Aims-To determine the anatomical site and underlying causes of blindness and severe visual impairment in children under 16 years of age in special education in the People's Republic of China with a view to determining potentially preventable and treatable causes. Methods-A national study of children attending schools for the blind in China was conducted between April and June 1998 using the WHO Prevention of Blindness Programme (WHO/PBL) eye examination record for children with blindness and low vision. Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 9 publications
7
61
0
1
Order By: Relevance
“…Researchers from other Asian countries 11,15,[21][22][23][25][26][27] have also reported that the underlying cause of visual loss cannot be determined in a high proportion of children. In our study, hereditary conditions, mainly retinal dystrophies, were the main identifiable group.…”
mentioning
confidence: 99%
“…Researchers from other Asian countries 11,15,[21][22][23][25][26][27] have also reported that the underlying cause of visual loss cannot be determined in a high proportion of children. In our study, hereditary conditions, mainly retinal dystrophies, were the main identifiable group.…”
mentioning
confidence: 99%
“…Studies in blind schools in developing countries have had a selection bias towards ocular disease. 14,15 While the presence of a multiple handicap unit within the Royal Blind School, Edinburgh reduced this bias, it is likely that some bias towards ocular disease remained.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the causes of childhood visual impairment in blind schools may have had a selection bias towards ocular disease. 14,15 The WHO/PBL methodology is a useful tool for international comparisons. While this study found that the method may be used in a developed setting, further work is required.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental eye anomalies, including anophthalmia and microphthalmia, are responsible for up to 25% of childhood visual impairment [Hornby et al, 1999[Hornby et al, , 2000. Clinical severity is variable, ranging from at its most severe, clinical anophthalmia (absent eye), through microphthalmia (congenitally small eye), to anomalies that only affect specific substructures of the eye.…”
Section: Introductionmentioning
confidence: 99%